Factors that influence income growth in listed plantation companieson the indonesian stock exchange - Lestari, Dewi; Fauzi, Indra (Jurnal Mantik, 2024)
Growth Income activity is Growth Income used to measure how effectively a company uses its assets. One way to measure Growth Income activity is to use Growth Income working capital turnover (WCTO) or Growth Income working capital turnover. The purpose of this study is to determine the Factors That Influence Growth Income in Plantation Companies Listed on the Indonesia Stock Exchange. The research method used by the author in this study is descriptive and quantitative. Based on the characteristics of the sampling, the companies that were sampled in this study were 10 companies out of 40 Plantation Sector companies listed on the Indonesia Stock Exchange during 2021-2023. Based on the influence of each variable simultaneously, it can be seen that the F count value (5.652)> F table (3.35) with a significance level of 0.105 <0.05 . So this shows that H3 is accepted Working Capital Turnover and Debt to Equity Ratio have a significant effect on Growth Income. Based on the analysis results, Working Capital Turnover has a significant effect on Growth Income, indicating the effectiveness of management in using assets to generate sales. However, Debt to Equity Ratio does not show a significant effect on Growth Income, although this ratio is important for assessing the company's financial risk